2020
DOI: 10.1080/14786419.2020.1837806
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition and phytotoxic activity of the essential oil of Artemisia sieversiana growing in Xinjiang, China

Abstract: The chemical composition and phytotoxic activity of the essential oil extracted from Artemisia sieversiana was investigated. In total 17 compounds were identified by GC/MS, representing 99.17% of the entire oil, among which α-thujone (64.46%) and eucalyptol (10.15%) were the most abundant constituents. The major components, their mixture as well as the essential oil exhibited significant phytotoxic activity against Amaranthus retroflexus, Medicago sativa, Poa annua and Pennisetum alopecuroides, with the IC 50 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…Previously, there were reports on the phytotoxic/allelopathic potential of volatile oils produced by Artemisia species. Jiang et al studied the chemical profile and phytotoxic activity of the essential oil extracted from A. sieversiana , which led to the identification of α-thujone (64.46%) and eucalyptol (10.15%) as the most abundant constituents [ 56 ]. Both the major oil components and the essential oil possessed significant phytotoxic effect against the receiver species A. retroflexus , Medicago sativa , P. annua and Pennisetum alopecuroides , with their IC 50 values ranged from 1.55~6.21 mg/mL (α-thujone), 1.42~17.81 mg/mL (eucalyptol), 0.23~1.05 mg/mL (the mixture of α-thujone and eucalyptol) and 1.89~4.69 mg/mL (the essential oil).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, there were reports on the phytotoxic/allelopathic potential of volatile oils produced by Artemisia species. Jiang et al studied the chemical profile and phytotoxic activity of the essential oil extracted from A. sieversiana , which led to the identification of α-thujone (64.46%) and eucalyptol (10.15%) as the most abundant constituents [ 56 ]. Both the major oil components and the essential oil possessed significant phytotoxic effect against the receiver species A. retroflexus , Medicago sativa , P. annua and Pennisetum alopecuroides , with their IC 50 values ranged from 1.55~6.21 mg/mL (α-thujone), 1.42~17.81 mg/mL (eucalyptol), 0.23~1.05 mg/mL (the mixture of α-thujone and eucalyptol) and 1.89~4.69 mg/mL (the essential oil).…”
Section: Discussionmentioning
confidence: 99%
“…Eucalyptol and camphor (purity 98%) were purchased from Sigma-aldrich Co. (St. Louis, USA). The volatile oils, eucalyptol, camphor and their mixture were diluted in 0.5% acetone in distilled H 2 O to yield 0.2, 0.5, 1.5, 3, 5 mg/mL solutions, with acetone as the initial solvent (our previous experiment showed acetone at such concentration did not significantly affect seedling growth of the test plants [ 37 , 56 ]. Five ml of 0.5% acetone in distilled H 2 O (control) or diluted solutions were added to each petri dish (9 cm in diameter) which contained 10 test seeds.…”
Section: Methodsmentioning
confidence: 99%
“…The EO of A. sieversiana was found to exhibit significant phytotoxic activity against Amaranthus retroflexus, Medicago sativa, Poa annua, and Pennisetum alopecuroides, with IC 50 values ranging from 1.89 -4.69 mg/mL. [16] Razavi et al reported that the EO of A. austriaca significantly reduced the seed germination, as well as the shoot and root length, of Lactuca sativa at concentrations higher than 1 mg/mL. [17] The EO of A. pedemontana (flowering stage) inhibited the root and leaf growth of Lolium perenne by 30 % at 0.4 μg/μL.…”
Section: Phytotoxic Activity Of the Eo And Its Major Constituentmentioning
confidence: 98%
“…[15] Volatiles produced by certain Artemisia species have been reported to be highly phytotoxic, and they are considered effective allelochemicals that favor the establishment of the plant's own dominance. [16][17][18] To learn more about volatiles released by plants, the classic Clevenger essential oil hydrodistillation and HS-SPME methods are often used to determine their chemical profiles. [19] Unlike HS-SPME, the HD method yields an EO which can be further used for bioactivity determination.…”
Section: Introductionmentioning
confidence: 99%
“…[33] The IC 50 for Artemisia sieversiana essential oil against A. retroflexus L. was 1.98, while it was 3.79 and 4.31 mg mL À 1 for its two major components α-thujone and eucalyptol, respectively, indicating the possible involvement of synergistic effect of these two compounds. [34] Worth noted, despite being less potent than the positive control 2,4-D isooctyl ester, AcOEtE as a natural herbicide has lots of advantages such as being health and environment friendly, and low cost, making it much interesting in organic farming practices. As far as we know, our present study represents the first report of the herbicidal effect of pomelo seed.…”
Section: Herbicidal Activitymentioning
confidence: 99%